Can ritual form be predicted from religious belief? A test of the Lawson-McCauley hypotheses - Malley, B; Barrett, J (Dr. Stewart and Prof. Strathern, co-editors, Journal of Ritual Studies, 2003)
Can ritual form be predicted from knowledge of religious beliefs? E. Thomas Lawson and Robert N. McCauley (Lawson & McCauley 1990; McCauley & Lawson 2002) have proposed a cognitive theory of religious ritual according to which the way in which superhuman agents are implicated in the ritual's action structure has consequences for the repeatability, reversibility, and relative sensory pageantry of the ritual in a religious system. We tested their predictions by systematic interviews of participants in the Hindu, Jewish, and Islamic traditions as represented on the campus of the University of Michigan. The Lawson-McCauley predictions were strongly supported by our findings, but our research also raised questions about the causal mechanism they propose, as few of our informants seemed to have clear ideas about the way in which superhuman agents were connected to their rituals.